2017
DOI: 10.1177/0306624x17741250
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Recidivism With the Youth Level of Service/Case Management Inventory (Reduced Version) in a Sample of Young Spanish Offenders

Abstract: Intervention in youth recidivism is critical in helping prevent young people from continuing their criminal career into adulthood, on a life-course-persistent trajectory. Andrews and Bonta attempt to provide an explanation of risk and protective factors using a conversion of the Youth Level of Service/Case Management Inventory (YLS/CMI), which predicts recidivism. In this study, scores have been obtained from 382 adolescents ( M age = 16.33 years) from the juvenile court, to check the ability of a reduced vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…This potential association of personality traits, antisocial personality disorder and psychopathy in delinquents requires further research. Interestingly, grade point average as a covariate was significantly related to Negative Valence and rejection by mother, thus confirming the importance of education in understanding criminal recidivism in juveniles, as has also been reported in other studies (Cuervo & Villanueva, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This potential association of personality traits, antisocial personality disorder and psychopathy in delinquents requires further research. Interestingly, grade point average as a covariate was significantly related to Negative Valence and rejection by mother, thus confirming the importance of education in understanding criminal recidivism in juveniles, as has also been reported in other studies (Cuervo & Villanueva, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Criminal recidivism may initially occur in youth, and a general rule states that the more an individual is antisocial, the earlier antisocial behavior occurs (DeLisi et al, 2013;Rhee et al, 2013). Recent data (Durose, Cooper, & Snyder, 2014) from the U.S. and Europe (Cuervo & Villanueva, 2018) are alarming due to warning of high recidivism among juvenile delinquents and the threat of recidivism in the further development of criminal behavior among young people.…”
Section: Highlightsmentioning
confidence: 99%
“…Few studies have analyzed the validity of the YLS/CMI in populations outside the Anglo-Saxon countries. Nonetheless, these few studies showed strong predictive validity for the YLS/CMI according to Rice and Harris’s (2005) classification in Asian (Benuto et al, 2014; Chu et al, 2015; Mori et al, 2017), Spanish (Cuervo & Villanueva, 2015, 2018), Portuguese (Pimentel et al, 2015), or Dutch populations (De Ruiter & Hildebrand, 2009). Nevertheless, some specific dimensions, such as Prior Criminal History and Substance Abuse, lacked content representativeness and predictive validity and the risk score means were lower than those on Anglo-Saxon countries (Takahashi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After receiving the institutional review board approval, the research team selected all participants (youth and parent/guardians) by using purposive sampling (Creswell, 1998), primarily for their ability to provide information that reflected the needs of county high-risk youth and their interest in the well-being of these youth. HHS personnel circulated an electronic flyer detailing the focus of the study to county-funded organizations, such as community mental health centers, hospitals, schools, and homeless shelters, and arranged for focus groups to be held in those organizations' own settings.…”
Section: Sampling Procedures and Instrumentmentioning
confidence: 99%
“…A high-crime, disadvantaged neighborhood may influence a positive parent and child relationship and expose youth to criminal behavior. Poor quality education, academic failure, underachievement, high absenteeism, and a sporadic attendance pattern have been linked to delinquency, especially violent delinquency (Cuervo & Villanueva, 2018;Lane & Carter, 2006). Due to no-or low-tolerance school policies, youth with educational issues face a more punitive approach, which leads to criminal involvement with juvenile court and paves the way for the school-to-prison pipeline (Mallett, 2016).…”
mentioning
confidence: 99%